A Variation Study of the Bearing Designs of a Covering of the Designed Building of the II Level of Responsibility Span of 24 m. - M. Rzaeva, Sabina; Lida, Lida; V. Rzaeva, Tatiana; V. Zonina, Svetlana (International Journal of Engineering and Technology, 2018)
In this work were considered the sequence of calculation of a metal-wooden farm of a segment outline, according to the set of rules "Wooden glued and whole wooden designs" Construction Norms and Regulations II - 25 - 80 (the joint venture 64.13330 - 2011) [1], "Steel structures" Construction Norms and Regulations of II - 23 - 81 (the joint venture 64.13330 - 2011) and Construction Norms and Regulations 2.01.07-85 "Loadings and influences" [2] for calculation of a metal farm with a trapezoid outline.The comparative analysis of calculations of loading of a body weight of farms, calculation of evenly distributed constant of the loading located on all flight, calculation of distributive snow loading is carried out. Settlement efforts in elements of farms are determined by method of cutting knots, longitudinal forces of N and the selections and check of sections of farms bending M. Derived moments are calculated in panels of the top belt. Owing to, the above-stated calculations a positive assessment of a possibility of design of the building with flight of 24 m is given, when calculating of the bearing designs on the greatest possible loadings where as a covering are offered metal-wooden segment and metal a trapezoid outline of a farm. According to the carried-out calculations, sections are picked up truly and undergo testing on all groups of limit conditions of building constructions, but after calculation of a consumption of material on designs of farms, it turned out that it is economically effective for design of the bearing designs of coverings to use a metal-wooden farm. Â Â